(untitled) (Medico Legal Update, 2021)
This study aimed to identify the influences of mohers’ parenting attitude, parenting efficacy, and stress levels on children’s social skills. A total of 117 mothers rearing 4–7-year-old children were included in this study. Data were collected using as elf-administered questionnaire from November 13 to 26, 2011. Collected data were analyzed using the IBM SPSS 20.0 program with descriptive statistics, t-test, one-way analysis of variance (scheffetestforpost-hoc), Pearson’s correlation, and multiple regressions. Mothers’ parenting attitude (permission) and efficacy were positively correlated, whereas mothers’ stress level was negatively correlated with children’s social skills. Children’s social skills were influenced by mothers’ parenting and marital stress levels and children’s gender and birth order. In addition, mothers’ occupational so influences children’s social skills. These results indicated that differences in gender and birth order should be considered in providing interventions for mothers’ stress management.